2015
DOI: 10.3892/mmr.2015.4069
|View full text |Cite
|
Sign up to set email alerts
|

Geranylgeranylacetone attenuates hepatic fibrosis by increasing the expression of heat shock protein 70

Abstract: Increasing evidence has demonstrated that the heat shock protein 70 (HSP70) gene may be closely associated with tissue fibrosis; however, the association between HSP70 and liver fibrosis remains to be fully elucidated. The present study hypothesized that geranylgeranylacetone (GGA) exerts beneficial effects on liver fibrosis though upregulation of the expression of HSP70. Liver fibrosis was induced in rats using carbon tetrachloride (CCl4). The rats were subsequently divided into three groups: Control group, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
(33 reference statements)
1
10
1
Order By: Relevance
“…The ability of GGA to induce HSP upregulation in several organs is well known [ 25 , 26 ]. Although He et al had indicated that the upregulation of HSP70 by GGA was associated with the suppression of fibrogenesis in the mouse liver [ 16 ], we did not find evidence of GGA-induced HSP70 upregulation in LX2 cells. These discrepancies may have resulted from the difference in the cell lines.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The ability of GGA to induce HSP upregulation in several organs is well known [ 25 , 26 ]. Although He et al had indicated that the upregulation of HSP70 by GGA was associated with the suppression of fibrogenesis in the mouse liver [ 16 ], we did not find evidence of GGA-induced HSP70 upregulation in LX2 cells. These discrepancies may have resulted from the difference in the cell lines.…”
Section: Discussioncontrasting
confidence: 99%
“…GGA treatment is known to induce upregulation of HSP family proteins in several organs. Previously, it was shown that GGA treatment in mice upregulated HSP70 levels in a liver specimen and was associated with suppression of liver fibrosis [ 16 ]. Therefore, we measured HSP70 expression in LX2 cells treated with GGA by western blot, and found that treatment with GGA for 24 h did not significantly change HSP70 expression compared to controls (Additional file 1 : SD).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GGA has been reported to induce overexpression of HSPs in stress conditions, whereas the induction effect is weak in the absence of stimulation, which suggests that GGA has few side effects. It has been demonstrated that GGA elicits multiple organ protection by increasing the expression of HSPs in response to hypoxia, ischemia, oxidation, toxins, and inflammation . In 2001, Ooie et al found that GGA given via the oral route can render cardioprotection against IRI by inducing HSP72 expression in rat hearts.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that GGA elicits multiple organ protection by increasing the expression of HSPs in response to hypoxia, ischemia, oxidation, toxins, and inflammation. [34][35][36][37] In 2001, Ooie et al 19 found that GGA given via the oral route can render cardioprotection against IRI by inducing HSP72 expression in rat hearts. Based on their study, there has been increasing interest in the cardiovascular protective effects and underlying mechanism of action of GGA.…”
mentioning
confidence: 99%